2019
DOI: 10.3390/genes10070542
|View full text |Cite
|
Sign up to set email alerts
|

Variable Number Tandem Repeats in the Mitochondrial DNA of Lentinula edodes

Abstract: Variable number tandem repeats (VNTRs) in mitochondrial DNA (mtDNA) of Lentinula edodes are of interest for their role in mtDNA variation and their application as genetic marker. Sequence analysis of three L. edodes mtDNAs revealed the presence of VNTRs of two categories. Type I VNTRs consist of two types of repeat units in a symmetric distribution, whereas Type II VNTRs contain tandemly arrayed repeats of 7- or 17-bp DNA sequences. The number of repeat units was variable depending on the mtDNA of different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…60 The tandem repeats in animals and plants have been reported to be involved in mtDNA stability by insertion and deletion of the repeat array. 61 Thus, it is not excluded that the decreased number of repetitive elements in one of the examined dogs might be a result of such slippage during replication. The in silico analyses revealed that there might be a 313 bp-long CpG island at the positions 16 137…16 449 (%GC = 0.40) in the canine mitochondrial VNTR region, which in some circumstances might be methylated or demethylated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 The tandem repeats in animals and plants have been reported to be involved in mtDNA stability by insertion and deletion of the repeat array. 61 Thus, it is not excluded that the decreased number of repetitive elements in one of the examined dogs might be a result of such slippage during replication. The in silico analyses revealed that there might be a 313 bp-long CpG island at the positions 16 137…16 449 (%GC = 0.40) in the canine mitochondrial VNTR region, which in some circumstances might be methylated or demethylated.…”
Section: Discussionmentioning
confidence: 99%
“…VNTRs are thought to have arisen due to slippages during DNA replication or as a consequence of unequal crossing‐over, and due to the repetitive nature of the sequence have allowed further increases/decreases in the number of repeats resulting in the polymorphisms observed 60 . The tandem repeats in animals and plants have been reported to be involved in mtDNA stability by insertion and deletion of the repeat array 61 . Thus, it is not excluded that the decreased number of repetitive elements in one of the examined dogs might be a result of such slippage during replication.…”
Section: Discussionmentioning
confidence: 99%
“…But at the same time, GHA79 has gained unique TR regions and lost a common TR region (Supplementary Excel File 2). Comparative analysis of the mitogenomes from three isolates of L. edodes, another Agaricales also revealed variable number TR regions (Kim et al, 2019). The authors proposed that the elongation of the repeat regions occurs through reciprocal incorporation of basic repeat units.…”
Section: Mitogenome Size Variation and Sources Of Genome Expansionmentioning
confidence: 99%
“…Ustilago maydis also shows uniparental inheritance associated with a defined mating type, where the result is strongly affected by mating-type locus ( Xu et al, 2000 ; Yan and Xu, 2003 ; Fedler et al, 2009 ). In the mating of filamentous basidiomyceteous fungi, two types of dikaryotic cells, which carry one of the two mtDNAs originated from the two monokaryotic cells, are generated through reciprocal entrance of nuclei to the cytoplasms of monokaryotic cells after hyphal fusion between monokaryotic hyphae with compatible mating types ( Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic diversity analysis using the mating type genes of 127 strains of L. edodes showed a high degree of diversity particularly in the A mating type locus of the wild strains ( Ha et al, 2018 ). The diverse nature of the A mating type genes enabled the discrimination of nuclei in dikaryons as well as monokaryons of different origins ( Kim et al, 2019 ). The mtDNA is another source of genetic information.…”
Section: Introductionmentioning
confidence: 99%